Astragaloside IV alleviates heart failure by promoting angiogenesis through the JAK-STAT3 pathway - Yan-Bo Sui (Taylor & Francis Group, 2019)
Context: Heart failure (HF) is one of the most serious diseases worldwide. Astragaloside IV (ASI) is widely used for the treatment of cardiovascular disease in China. Objective: To evaluate the protective effect of ASI on the HF in a Sprague–Dawley rat model of left coronary artery ligation, and investigate the angiogenesis-related mechanisms. Materials and methods: Left coronary artery was ligated to induce a rat model of HF, and the rats were treated with vehicle (saline) or different doses of ASI (0.1, 0.3 and 1 mg/kg/day) by oral gavage for 6 weeks. Cardiac function was evaluated by echocardiography. Infarct size was determined by triphenyltetrazolium chloride staining. Cardiac vascular density was analyzed by microangiography. Real-time PCR, Western blot and chromatin immunoprecipitation were performed to investigate the mechanisms. Results: ASI treatment improved the body weight and survival rate of HF rats, as well as the cardiac function of HF rats, with significantly improved ejection fraction (75.27 ± 5.75% vs. 36.26 ± 4.14%) and fractional shortening (45.39 ± 3.66% vs. 17.88 ± 1.32%). ASI reduced the infarct size of the HF rats by 47%. ASI promoted angiogenesis, with increased vascular density (2.08-fold) and induced mRNA expression of CD31 (1.81-fold) and VEGF (2.70-fold) in the ischemic heart. Furthermore, ASI induced the phosphorylation of JAK (1.89-fold) and STAT3 (2.95-fold), as well as the activity of VEGF promoter which was regulated by STAT3. Discussion and conclusions: ASI alleviated HF by promoting angiogenesis through JAK-STAT3 pathway, providing novel alternative strategies to prevent HF in the future.